PERANCANGAN SISTEM INFORMASI PENJUALAN TIKET KOLAM RENANG YONIF 136 BERBASIS WEBSITE - Renata Hutasoit; Silalahi, Mesri (LPPM Universitas Putera Batam, 2022)
Tourist attractions such as the Infantry Battalion 136 swimming pool, which is located in the Batu Aji area of ​​Batam City, are open every day from 10.00 WIB to 17.00 WIB. This Yonif swimming pool uses ticket sales manually, which causes officers to experience problems in filling in visitor data when tourists are crowded, causing crowds because the place is inadequate. The researcher aims to help the Infantry Battalion pool on how to design website-based ticket sales. The researcher will conduct this research using the waterfall method. The result of this research is that the Yonif swimming pool will be easier and more practical in ticket sales and visitor data input.